(untitled) - Jordaan, Hannelet

An efficiency and economic comparison of conventional and radio frequency identification slaughter readiness methodology in commercial lamb feedlots (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.